Behold the Lessons of Brutus: The Federal Judiciary and the Specter of Consolidation - Skeen, Michael (Colloquium: The Political Science Journal of Boston College, 2017)
It has often been noted that the lasting legacy of the Anti-Federalists is the Bill of Rights. What is less known are the Anti-Federalists’ fears about the federal judiciary—most specifically about the role of the Supreme Court in the new constitutional regime. In this essay, we will explore a line of reasoning advanced by an Anti-Federalist author by the pen name Brutus. Brutus was deeply worried about the judicial branch employing judicial review to consolidate the various state governments into a single, national authority. Of course, the states have not disappeared; consolidation has not been an open-ended and consistent development. However, in many instances, the lessons of Brutus have certainly proven themselves to be prescient.